2003
DOI: 10.1071/fp03020
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythm of stem and fruit diameter dynamics of Japanesepersimmon (Diospyrus kaki Thunb.) is affected by deficiency of water in saline environments

Abstract: Early diagnosis of water deficiency is essential to mitigate salt stress injury in plants. The effects of salt stress during the fruit growth stage on stem and fruit diameters of Japanese persimmon trees (Diospyrus kaki Thunb.) were measured by a micromorphometric technique under greenhouse conditions. This technique is less cumbersome and more precise in comparison to measurement of water potential in a small pressure chamber. The effect of stress was measured on photosynthetic rate, pre-dawn water potential,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
10
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 22 publications
7
10
0
Order By: Relevance
“…Night-time closure of the stomata improved water potential and encouraged assimilate partitioning into the fruits. This is consistent with the results of Ito et al (2002) in Japanese pear, Fujita et al (2003a) in Japanese persimmon, and Moghaieb et al (2006) in tobacco, in which fluctuations in the circadian rhythm of stem diameter and pod thickness was mainly regulated by the water status.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Night-time closure of the stomata improved water potential and encouraged assimilate partitioning into the fruits. This is consistent with the results of Ito et al (2002) in Japanese pear, Fujita et al (2003a) in Japanese persimmon, and Moghaieb et al (2006) in tobacco, in which fluctuations in the circadian rhythm of stem diameter and pod thickness was mainly regulated by the water status.…”
Section: Discussionsupporting
confidence: 93%
“…The night recovery of pod thickness continued to decrease with the passage of time because the organ failed to gain water under stressed conditions. The correlations between circadian rhythm changes in stem and fruit diameters and water potential of the organs were recorded previously in tomato (Johnson et al 1992, Fujita et al 2003a. It was suggested that low water potential of the plant during the daytime reduced phloem turgor and thereby decreased the driving force for sap flow into the fruit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3D). Similar observations were also determined by Fujita et al (2003) who reported that leaf gas exchange parameters of D. kaki were significantly reduced under salinity stress. Salinity affects plant growth due to changes in many physiological processes including photosynthesis (Kalaji and Pietkiewicz, 1993;Kalaji and Guo, 2008).…”
Section: Plant Material Salinity Treatment and Salt Stress Symptom Ssupporting
confidence: 78%
“…Besides there are only few studies carried out to determine the response of persimmon rootstocks to salinity stress by assessing gas exchange, to our knowledge. Fujita et al (2003) measured the effects of salinity stress on photosynthetic rate, pre-dawn water potential, stomatal conductance, transpiration and Na and K contents of D. kaki leaves. The author indicated that salt stress reduced water potential, photosynthesis, transpiration and stomatal conductance.…”
Section: Experimentation and Data Analysismentioning
confidence: 99%